2016
DOI: 10.1007/s12160-016-9828-2
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Messages Increase Dairy Consumption in Adults: a Randomized Controlled Trial

Abstract: Taken together, it appears as though ensuring message content is targeted to the specific population's beliefs and motives is of importance when developing behavioral change intervention material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 33 publications
(33 reference statements)
1
8
0
Order By: Relevance
“…In this study, participants were presented with brief messages on a website on four consecutive days. Other studies (Bassett-Gunter et al, 2013;Hatchell, Bassett-Gunter, Clarke, Kimura, & Latimer-Cheung, 2013;Jung, Latimer-Cheung, Bourne, & Martin Ginis, 2017) using a similar methodology also reported mixed and limited effects of framed and/or risk messages. Reading messages on a website may not be very engaging for participants.…”
Section: Discussionmentioning
confidence: 89%
“…In this study, participants were presented with brief messages on a website on four consecutive days. Other studies (Bassett-Gunter et al, 2013;Hatchell, Bassett-Gunter, Clarke, Kimura, & Latimer-Cheung, 2013;Jung, Latimer-Cheung, Bourne, & Martin Ginis, 2017) using a similar methodology also reported mixed and limited effects of framed and/or risk messages. Reading messages on a website may not be very engaging for participants.…”
Section: Discussionmentioning
confidence: 89%
“…Previous research has demonstrated the effectiveness of targeted interventions based on Social Cognitive Theory in increasing volitional dairy consumption in young women ( 23 ) and adults aged 30–50 years ( 24 ) . Targeted interventions involve the development of material specific to a subset of the population, rather than specific to each individual, and thus have the potential to reach large numbers of people within the targeted subset at a relatively low cost.…”
mentioning
confidence: 99%
“…Sub-groups of the population that may need special focus may still benefit from these messages but would likely need more customized and tailored communication. Past work has tended to focus on either on one aspect of message design or on a small set of behaviors or a more defined population group [34][35][36][37][38][39]. These studies differ from the current research in having more focused goals as part of a directed behavior-change intervention.…”
Section: Messages Refined Post Content Validitymentioning
confidence: 91%